2014
DOI: 10.1038/npp.2014.84
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dopamine D2 Receptors in Human Reinforcement Learning

Abstract: Influential neurocomputational models emphasize dopamine (DA) as an electrophysiological and neurochemical correlate of reinforcement learning. However, evidence of a specific causal role of DA receptors in learning has been less forthcoming, especially in humans. Here we combine, in a between-subjects design, administration of a high dose of the selective DA D2/3-receptor antagonist sulpiride with genetic analysis of the DA D2 receptor in a behavioral study of reinforcement learning in a sample of 78 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
134
4
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(152 citation statements)
references
References 71 publications
11
134
4
3
Order By: Relevance
“…Computational models can guide the investigation of specific mechanisms that might generate individual differences in learning performance in such experiments (e.g., Cavanagh et al, 2010;Eisenegger et al, 2014;Krugel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Computational models can guide the investigation of specific mechanisms that might generate individual differences in learning performance in such experiments (e.g., Cavanagh et al, 2010;Eisenegger et al, 2014;Krugel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We manipulated dopamine in a placebo-controlled, withinsubjects manner using the selective D2/D3 receptor antagonist sulpiride. Sulpiride has previously been shown to modulate learning (Eisenegger et al, 2014;Mehta et al, 2008;van der Schaaf et al, 2014) as well as brain and behavioral responses to reward and punishment (Becker et al, 2013;Jocham et al, 2014;McCabe et al, 2011). Our primary interest was in the comparison of near-miss and full-miss events.…”
Section: Introductionmentioning
confidence: 99%
“…Dopaminergic medication was either levodopa or dopamine agonists which address different dopaminergic receptors (Brusa et al 2005;Cox et al 2015;Dirnberger and Jahanshahi 2013;Moustafa et al 2013;Vaillancourt et al 2013). For example, Eisenegger et al (2014) reported that administering the dopamine D2/D3 receptor agonist sulpride impairs choice performance but not learning. In contrast, levodopa leads to a non-specific increase in brain dopamine level (Eisenegger et al 2014).…”
Section: Discussionmentioning
confidence: 99%